Exposure to cotton dust in an experimental cardroom. Issue 3 (August 1984) - Haglind, P; Rylander, R
Abstract : Changes in respiratory function (FEV1) and polymorphonuclear neutrophils (PMN) on nasal epithelium were studied in 68 students and 39 cotton mill workers in an experimental cardroom. The exposure was characterised by the vertical elutriator dust and endotoxin levels. A dose related decrease was found for FEV1 which was more pronounced in smoking workers. The thresholds for no FEV1 reaction were 0.58 mg/m3 dust and 0.17 micrograms/m3 endotoxin for students and 0.43 mg/m3 and 0.08 micrograms/m3 for smoking workers. The PMN increased in most of the experiments but no dose response relationship could be shown. In experiments with smoking workers or when washed cotton was carded a better correlation was obtained between FEV1 decrease and endotoxin levels than for dust levels.